Oxidative stress in normal hematopoietic stem cells and leukemia. Issue 4 (25th March 2018) - Samimi, Azin; Kalantari, Heybatullah; Lorestani, Marzieh Zeinvand; Shirzad, Reza; Saki, Najmaldin
Abstract : Leukemia is developed following the abnormal proliferation of immature hematopoietic cells in the blood when hematopoietic stem cells lose the ability to turn into mature cells at different stages of maturation and differentiation. Leukemia initiating cells are specifically dependent upon the suppression of oxidative stress in the hypoglycemic bone marrow (BM) environment to be able to start their activities. Relevant literature was identified by a PubMed search (2000–2017) of English‐language literature using the terms 'oxidative stress, ' 'reactive oxygen species, ' 'hematopoietic stem cell, ' and 'leukemia.' The generation and degradation of free radicals is a main component of the metabolism in aerobic organisms. A certain level of ROS is required for proper cellular function, but values outside this range will result in oxidative stress (OS). Long‐term overactivity of reactive oxygen species (ROS) has harmful effects on the function of cells and their vital macromolecules, including the transformation of proteins into autoantigens and increased degradation of protein/DNA, which eventually leads to the change in pathways involved in the development of cancer and several other disorders. According to the metabolic disorders of cancer, the relationship between OS changes, the viability of cancer cells, and their response to chemotherapeutic agents affecting this pathway are undeniable. Recently, studies have been conducted to determine the effect of herbal agents and cancer chemotherapy drugs on oxidative stress pathways. By emphasizing the role of oxidative stress on stem cells in the incidence of leukemia, this paper attempts to state and summarize this subject.